AN EFFICIENT CONSTRUCTION OF 4-OXO-1,3-DIAZABICYCLO[3.3.0]OCTANES VIA THIOHYDANTOINS - KIM, IJ; YOO, KH; SHIN, KJ; KIM, DJ; PARK, SW (MARCEL DEKKER INC, 1995)
New stereoisomeric N-bridged heterocycles, 4-oxo-1,3-diazabicyclo[3.3.0]octanes(4) were synthesized from trans-4-hydroxy-L-proline(1). Thiohydantoins 3 as the key intermediates were prepared by nucleophilic addition of 1 to isothiocyanates, and subsequent cyclization. These thiohydantoins 3 were readily desulfurized to provide 4.